2017
DOI: 10.1111/jfd.12610
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of metabolomic approach in infectious fish disease studies

Abstract: The approaches of transcriptomic and proteomic have been widely used to study host-pathogen interactions in fish diseases, and this is comparable to the recently emerging application of metabolomic in elucidating disease-resistant mechanisms in fish that gives new insight into potential therapeutic strategies to improve fish health. Metabolomic is defined as the large-scale study of all metabolites within an organism and represents the frontline in the 'omics' approaches, providing direct information on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…In previous studies, we have shown that this approach can detect differences in dietary interventions and the nutritional status of GSB [25, 26]. Metabolomics have been applied recently in several areas of aquaculture [27], including infectious fish diseases [24]. However, its application in fish parasitic diseases is very scarce, and only done thus far in naturally infected fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have shown that this approach can detect differences in dietary interventions and the nutritional status of GSB [25, 26]. Metabolomics have been applied recently in several areas of aquaculture [27], including infectious fish diseases [24]. However, its application in fish parasitic diseases is very scarce, and only done thus far in naturally infected fish.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics are emerging as a valuable tool to find biomarkers in many diseases, as the metabolome includes all small molecules that are present in a biological system and thus, metabolites serve as direct signatures of the metabolic responses and perturbations in metabolic pathways and tightly correlate with a particular phenotype. These properties make the serum metabolome an attractive minimally invasive technique for the identification of system phenotypic perturbations, especially those disruptions due to pathogens [23, 24], and it has started to be used in aquaculture to identify biomarkers indicative of physiological responses of living organisms to environmental or culture conditions [2527].…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture remains an important source of food and nutrition for millions of people worldwide, which plays an essential role in meeting the urgent global food demand (Low et al 2017 ). Pacific white shrimp, Litopenaeus vannamei , with the largest production in global shrimp industry, has suffered enormous economic losses due to serious infectious diseases (Zeng et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture remains an important source of food and nutrition for millions of people worldwide, which plays an essential role in meeting the urgent global food demand (Low et al, 2017). The pacific white shrimp, Litopenaeus vannamei, with the largest production by tonnage in the global shrimp industry (>4.1 million tons per year) (FAO, 2019), is currently facing challenges due to several diseases.…”
Section: Introductionmentioning
confidence: 99%